Policy Implementation of Permen-KP RI Number 18 of 2021 on Small Pelagic Purse Seine Fishing Gear at PPP Muara Sungai Baturusa Kota Pangkalpinang - Taj, Kemal; Sudarmo, Agnes Puspitasari; Noviyanti, Rinda (Faculty of Law, Universitas Pekalongan, 2024)
The purpose of this research is to identify the implementation, identify the responses of fishermen and related stakeholders, analyze the problems, and recommend strategic solutions that will be offered to the central government regarding the capture fisheries business of small pelagic purse seine fishermen at PPP Muara Sungai Baturusa Kota Pangkalpinang after the issuance of PERMEN-KP RI Number 18 of 2021. The informants of this research are small pelagic purse seine fishermen and related stakeholders at the PPP Muara Sungai Baturusa Pangkalpinang City. The method used is descriptive qualitative. Data collection by direct observation and interviews. Data were analyzed by qualitative analysis and SWOT analysis. The results showed that the policy implementation of PERMEN-KP RI Number 18 of 2021 on small pelagic purse seine fishing gear has not gone well. The impact of the separation of authority has resulted in instability in the economy and social life of fishermen and related stakeholders. Fishermen become afraid to fish > 12 nautical miles because they will definitely be prosecuted/arrested by fisheries supervisory officers. With all the consequences if the policy is not reviewed by the central government, in the future it is likely that many small pelagic purse seine vessels at PPP Muara Sungai Baturusa Kota Pangkalpinang will experience bankruptcy.